DAMPAK GREEN SUPPLY CHAIN MANAGEMENT TERHADAP KINERJA BISNIS (INBOUND PERSPECTIVE) - Wahyudi Henky Soeparto; Elvina Emanuella Br Surbakti (Fakultas Ekonomi Universitas 45 Surabaya, 2021)
Industry has a positive impact on the economy aspect in Indonesia. However, the positive impact is not balanced with the problem solving that can be caused by the industry. Business performance is one of the criterion carried out to measure the achievement of a business obtained through production activities derived from business organizations (Agus et al., 2017). Green procurement focuses on social complexity, which means that green procurement can evolve that is tailored to the capabilities of partner companies enabling companies to access resources from their partners (Wong et al., 2017). Green manufacturing is one of the most important factors for business performance applied by the company, green manufacturing is an activity implemented with the aim of eliminating environmental waste to reduce environmental impacts and improve ecological efficiency (Leme et al., 2018). In addition, there is a growing emphasis for manufacturing companies to adopt Green Operation strategies to reduce negative environmental impacts (Liu et al., 2017). This research aims to test the influence of green procurement, green manufacturing, green operation on business performance.